The Relationship between Anxiety Level and Sleep Quality in Patients Lower Extremity Fracture Postoperative: Hubungan Kecemasan Dengan Kualitas Tidur Pasien Pos Operasi Fraktur Ekstremitas - Setianingsih, Endah; Putri, Erika; Waladani, Barkah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Background: A common problem often faced by patients post fracture surgery is often sleep disturbances. Factors that influence sleep disorders in fracture patients are pain and anxiety. Sleep disorders can affect the quality of sleep in patients. Research Objective: To determine the relationship between anxiety and sleep quality in post-operative fracture patients in the Inpatient Room at PKU Muhammadiyah Gombong Hospital. Research Method: The research method is correlational with a cross-sectional approach. The author took data from 61 patients taken by purposive sampling. Data collection techniques were interviews using questionnaires. Data analysis in this research includes univariate analysis (descriptive analysis) and bivariate analysis using the chi square test. The results of the study state that there is a relationship between anxiety and sleep quality in post-op fracture patients, p value (0.001). Recommendation: Future research provides interventions to overcome sleep disorders in post-op fracture patients.